1963
DOI: 10.1038/icb.1963.56
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Mechanism of Cation Transport

Abstract: SUMMARY.Membrane-bound cation stimulated adenosine-triphosphatase is thought to be closely associated with active ion transport phenomena. As this enzyme system requires the combination of both sodium and potassium ions for full activation its mechanism of action has been investigated under these conditions. Using adenosine triphosphate labelled with P^ô nly in the terminal position as substrate for the reaction we have been able to show that ATP^2 is hydroiysed to adenosine diphosphate and radioactive orthoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1965
1965
1975
1975

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Formation of this complex is stimulated by Na+ but not K+; when both ions are present the steady-state concentration of 32p_ labelled phosphoprotein complex is greatly decreased whereas the hydrolysis of [y-32P]ATP is enhanced. Most investigators have concluded that the 32P-labelled phosphoprotein complex recovered in these experiments is an acyl-phosphate-enzyme derivative that functions as an intermediate (E P) during the hydrolysis ofATP by (Na+ + K+)activated ATPase (Charnock, Rosenthal & Post, 1963;Nagano et al 1965;Bader, Sen & Post, 1966).…”
mentioning
confidence: 98%
“…Formation of this complex is stimulated by Na+ but not K+; when both ions are present the steady-state concentration of 32p_ labelled phosphoprotein complex is greatly decreased whereas the hydrolysis of [y-32P]ATP is enhanced. Most investigators have concluded that the 32P-labelled phosphoprotein complex recovered in these experiments is an acyl-phosphate-enzyme derivative that functions as an intermediate (E P) during the hydrolysis ofATP by (Na+ + K+)activated ATPase (Charnock, Rosenthal & Post, 1963;Nagano et al 1965;Bader, Sen & Post, 1966).…”
mentioning
confidence: 98%